NUMERICAL MODELLING ON VEHICLE DYNAMIC STABILITIES IN LOW-LYING FLOOD AREAS - SUET TING , SAMANTHA LIM (Universiti Teknologi PETRONAS, 2018)
Vehicle instability can be simply described as the state whereby vehicle are compromised by instability and it can be represented in three forms; sliding, floating and most recently, toppling motions. Unfortunately, studies pertaining to understand the behaviour of vehicles stability (both in motion and at rest) in floodwater flow, remains largely unexplored and essentially, none for the case of moving vehicles. Hence, the primary aim of this paper aims to develop a numerical solution for the vehicle in low-lying flood area as well as to analyse the response of the hydrodynamic parameters on the vehicle stability. In reference to that, what is the response of the corresponding hydrodynamic parameters on a vehicle? Within this research project, the type of vehicle that was considered was a Perodua Viva and a slope grade of 0.5% will be made the low lying slope road dimensions. Other than that, a perpendicular flow orientation in respect to the vehicle was considered, and defined the hydrodynamic parameters or water depth and velocity to be 0.7 m and 0.01 m/s respectively. The software that were employed throughout the span of this project were SolidWorks and ANSYS Fluent. It is to be informed that since the existing studies on this subject manner remains sparse and incomplete, the main challenges of this project heavily lies in the lack of methodology references and the time-consuming simulation process. Existing references of research papers proved to be inadequate as the simulation set up not only insufficient but lacked variety in terms of the state of the vehicle (stationary). Due to the simulation software’s complex, time consuming and heavy-processing nature, efforts to carry out full simulation using the available resources provided, arriving to the final outcomes that the work remains a challenge, even at the present time. However, even at that, it could be conclusively proven that vehicle instability failure mechanisms (in terms of sliding or toppling) had taken place in this research, considering the perpendicular flow orientation, water velocity and depth